1996
DOI: 10.1046/j.1471-4159.1996.67010398.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP‐Activated Nonselective Cation Current in NG108‐15 Cells

Abstract: ATP (1 mM) induced a biphasic increase in intracellular Ca 2~concentration ([Ca2~]), i.e., an initial transient increase decayed to a level of sustained increase, in NG108-15 cells. The transient increase was inhibited by a phospholipase C inhibitor, 1-[6-[17~-3methoxyestra-1,3, 5(10)-trien -1 7-yl]amino]hexyl]-1Hpyrrole-2,5-dione (U73122), whereas the sustained increase was abolished by removal of external Ca2~.We examined the mechanism of the AlP-elicited sustained [Ca2~], increase using the fura-2 fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…The rank order of agonist potency to induce this current was BzATP 2-methylthio-ATP > ATP > adenosine 5'-O-(3-thiotriphosphate)~°ADP. These properties of the P2X7 receptor are similar to those of the P2Z receptor in NG1O8-i5 cells (Kaiho et a!., 1996).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…The rank order of agonist potency to induce this current was BzATP 2-methylthio-ATP > ATP > adenosine 5'-O-(3-thiotriphosphate)~°ADP. These properties of the P2X7 receptor are similar to those of the P2Z receptor in NG1O8-i5 cells (Kaiho et a!., 1996).…”
supporting
confidence: 59%
“…Whole-cell voltage clamp analyses revealed that 1 mM ATP induced a nonselective cation current with an Erev of 9.3 ±1.2 mY (n = 22) in N18TG-2 cells, which was similar to that with an~of 12.5 ±0.8 mV (n = 10) in NG1O8-15 cells (Kaiho et al, 1996). In contrast, ATP at the same concentration did not induce the current in C6Bu-1 cells.…”
Section: Discussionmentioning
confidence: 57%
“…INS·P2X7 was measured using the whole-cell configuration of the patch-clamp technique (20) as descried previously (7,10,21). Patch pipettes had a tip resistance of about 2 MW when filled with an intracellular solution containing 110 mM CsOH, 30 mM CsCl, 50 mM DL-aspartic acid, 5 mM MgATP, 3 mM MgCl 2 , 5 mM potassium creatine phosphate, 10 mM EGTA and 20 mM HEPES (pH 7.2 with DL-aspartic acid).…”
Section: Whole-cell Clampmentioning
confidence: 99%
“…10; I. Matsuoka, unpubished result of the full length sequence) to that of mouse P2X7 receptor first cloned by Chessell et al (11) in NTW8 mouse microglial cells. A high concentration (>0.3 mM), but not a low concentration, of ATP activates a nonselective cation current, indicating that the only functional P2X receptor is the P2X7 receptor in NG108-15 cells (7,12,13). Rat and human P2X7 receptors transform themselves from channels to large pores by prolonged application of ATP (8,14), but this does not occur in mouse P2X7 receptors in NG108-15 cells (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation